A review of the impact of environmental factors on the fate and transport of coronaviruses in aqueous environments - Diplina Paul (Nature Portfolio, 2021)
Abstract The ongoing severe acute respiratory syndrome-coronavirus (SARS-CoV-2) has triggered the coronavirus pandemic (COVID-19) that has claimed hundreds of thousands of lives worldwide. This virus spreads predominantly by human-to-human transmission via respiratory droplets. However, the presence of this virus in the fecal and anal swabs of infected patients has triggered the need for research into its waterborne transmission. The various environmental factors that impact the persistence of coronavirus in different water matrices include temperature, UV exposure, organic matter, disinfectants as well as adversarial microorganisms. This review summarizes the most recent research data on the effect of various factors on coronavirus in aqueous environments. The available data suggest that: (i) increasing temperature decreases the overall persistence of the virus; (ii) the presence of organic matter can increase the survivability of coronavirus; (iii) chlorine is the most effective and economic disinfectant; (iv) membrane bioreactors in wastewater treatment plants are hosts of competitive microorganisms that can inactivate coronaviruses; (v) ultraviolet irradiation is another effective option for virus inactivation. However, the inactivation disinfection kinetics of coronaviruses are yet to be fully understood. Thus, further research is needed to understand its fate and transport with respect to the water cycle so that effective strategies can be adopted to curb its effects. These strategies may vary based on geographic, climatic, technical, and social conditions around the globe. This paper explores possible approaches and especially the conditions that local communities and authorities should consider to find optimal solutions that can limit the spread of this virus.